Амебейный агон в античной буколической поэзии и причины победы одного из певцов в Theocr. 5 и Verg. Ecl. 7 - Смирнова , Анна С. (Philologia Classica, 2007)
Comparison of amoebic competitions in antiquity (in Theocritus, anonymous poets from Corpus Theocriteum, Virgil, Calpurnius, unknown author of Einsiedeln Eclogues, and Nemesianus) allows defining traditional themes of verse, revealing particular qualities of composition, and listing three main ways to join in a song. Characterization of shepherd singers points at equality of their skills, and most of competitions end in a draw. This pattern is broken only in the fifth eclogue by Theocritus and in the seventh by Virgil, motives of the judge being obscure. The author of the article examines different hypothesis of reasons for one’s victory in such a competition and comes to a conclusion that the answer should be looked for in the poet’s basic idea.